MODIFIED KAOLIN WITH CATIONIC SURFACTANT FOR GIBBERELLIC ACID CARRIER MATERIALS - Sunardi Sunardi; Utami Irawati; Yateman Arryanto; Sutarno Sutarno (Universitas Gadjah Mada, 2011)
Synthesis of surfactant modified kaolin from natural kaolin from Tatakan, Tapin, South Kalimantan and its application for carrier material of gibberellic acid have been conducted. The kaolin modification was done by surface engineering using cationic surfactant cetyltrimethylammonium bromide (C16TMABr). The characterizations of kaolin and surfactant modified kaolin were carried out by XRF, SEM, XRD, FTIR and TGA/DTA. The adsorption capacity of kaolin was determined by Langmuir adsorption isotherm model. The result showed that kaolin from Tatakan, South Kalimantan consist of kaolinite, halloysite, quartz, chlorite, and christobalite. Surface modification using cationic surfactant showed that increasing surfactant content onto kaolin was proportional to the amount of surfactant loaded. Gibberellic acid was partitioned into the organic phase created by the surfactant tails of the C16TMA+ modified kaolin. The calculations result by Langmuir adsorption isotherm model showed that the highest increasing adsorption capacity occurred on surfactant modified kaolin with surfactant/CEC ratio of 2.0, with the adsorption capacity of 28.41 mg/g.